72.5k views
2 votes
Is this answer correct on problem 3

Is this answer correct on problem 3-example-1
User Iwasrobbed
by
5.6k points

2 Answers

3 votes
This is a vertical parabola which opens downwards

Use the formula

4p(y - k) = (x - h^2

converting to vertex form-
y =
-1/4(x^2 + 4x) + 3
y = -1/4[ (x + 2)^2] + 4

y - 4 = -1/4 (x + 2)^2

-4(y - 4) = (x + 2)^2 so the vertex is at (-2, 4)
comparing with the above formula
4p = -4
so p = -1 where p is the distance of the focus from the vertex
The vertex is at (-2,4) so the focus is at (-2, 4-1) = (-2, 3) Answer

User Sutto
by
5.5k points
4 votes
-1/4*x^2-x+3=-1/4*(x^2+4x)+3=-1/4*(x^2+4x+4)+4=-1/4*(x+2)^2+4
x0=-2
User Sachchidanand
by
5.8k points